Asian Long-Range Transport in Relation to Atmospheric Rivers in Northern California - Catherine N. Liu; Sen Chiao; Ju-Mee Ryoo (Atmosphere, 2019)
The study investigates the effect of aerosol long-range transport on precipitation over Northern California during atmospheric river (AR) events in the 2017 cold season (January−April). ARs in 2017 were one of the strongest to date, and the intense precipitation associated with the ARs resulted in flooding, destruction of property, and contamination of water supplies. The Aerosol Optical Depth (AOD) from Moderate Resolution Imaging Spectroradiometer (MODIS) data shows Asian dust traveling across the Northern Pacific Ocean along with AR events. Aerosol measurements in California, provided by the Interagency Monitoring of Protected Visual Environments (IMPROVE), show that more Asian dust tends to be observed over the coast, while non-Asian/localized dust is observed inland. A mixture of Asian and localized dust is observed over the mountains, although higher amounts of both are observed in the spring (March−April). Back trajectory analysis confirms that Asian aerosols are transported along the air parcels, and each AR event has its own transport pattern in terms of horizontal advection and vertical lifting. Correlation between precipitation and aerosols is low. This suggests that aerosols contribute little to the decrease of local precipitation during the 2017 AR events.